Results of chemotherapy in 30 AIDS patients with symptomatic pulmonary Kaposi's sarcoma. Issue 10 (October 1994) - Cadranel, J L; Kammoun, S; Chevret, S; Parrot, A; Denis, M; Winter, C; Carette, M F; Rozenbaum, W; Akoun, G M; Mayaud, C M
Abstract : BACKGROUND–The aim of this study was to report the effects of a three-drug chemotherapy regimen in patients with symptomatic AIDS-related pulmonary Kaposi's sarcoma and to analyse prognostic factors for survival. METHODS–Thirty consecutive HIV seropositive patients with respiratory symptoms and proven pulmonary Kaposi's sarcoma were treated with the same therapeutic regimen comprising adriamycin (30 mg/m2), bleomycin (10 mg/m2), and vincristine (2 mg) administered intravenously once every four weeks. RESULTS–Two patients died during the first course of chemotherapy. In the other 28 cases dyspnoea improved and Pao2 rose despite minimal (n = 17) or no (n = 11) improvement in the chest radiographic appearance. The median survival from the beginning of chemotherapy was 6.5 months. Poor prognostic factors for survival were: (1) absence of cutaneous Kaposi's sarcoma; (2) previous opportunistic infection; (3) CD4 cell count < 100/microliters; (4) leucocytes < 3500/microliters; (5) haemoglobin < 10 g/dl; and (6) absence of radiological response. Of the 28 patients 24 experienced at least one episode of neutropenia which was associated with bacterial infection in 16 cases. CONCLUSIONS–Chemotherapy may improve respiratory impairment in patients with extensive pulmonary Kaposi's sarcoma but the outcome remains poor. The efficacy of chemotherapy may be limited by neutropenia.